Authentic Texts: Their Advantages in Developing Students’ Language Awareness in ESP - Arwina Dharma (Universitas Negeri Padang, 2014)
This paper is to discuss the advantages of using authentic texts in teaching English as a Foreign Language. It is based on my experience in guiding learners studying English for Specific Purposes in Language Training Centre - Andalas University. The aim is to share experience with other English teachers as well as to enrich English teaching materials which are really suitable for the specific learners. The purpose of using authentic texts in teaching is to realize that the functions of language are often best understood in a discourse environment so that exploring language in context helps us to improve our understanding about forms and meanings of language.The discussion on this paper is divided into; the background, some principles on ESP, how to select materials, some limitation of published materials, and some advantages of using authentic texts. The focus on authentic texts can help learners to notice and analyze aspects of language usage which have gone unnoticed and untaught. It also provides them with insight of the real language use in the real situation. Furthermore, it helps the learners to recognize the role of aspects of culture in the texts since language and culture are inseparable. To conclude, real language use in a variety of natural occurring texts can help English teachers to develop students’ language awareness